ExoMol line lists – XXXVIII. High-temperature molecular line list of silicon dioxide (SiO2). Issue 2 (14th May 2020) - Owens, A; Conway, E K; Tennyson, J; Yurchenko, S N
ABSTRACT: Silicon dioxide (SiO2 ) is expected to occur in the atmospheres of hot rocky super-Earth exoplanets but a lack of spectroscopic data is hampering its possible detection. Here, we present the first, comprehensive molecular line list for SiO2 . The line list, named OYT3, covers the wavenumber range 0 – 6000 cm −1 (wavelengths λ > 1.67  μ m) and is suitable for temperatures up to T  = 3000 K. Almost 33 billion transitions involving 5.69 million rotation–vibration states with rotational excitation up to J  = 255 have been computed using robust first-principles methodologies. The OYT3 line list is available from the ExoMol data base at www.exomol.com .